Exploring connections: Reflections on mother-tongue education in postcolonial Uganda - Ssentanda, Medadi E (Stellenbosch University, 2014)
Mother-tongue (MT) education in Uganda, like in many other countries, is a highly contentious subject. A plethora of problems plague MT education and all are similar to those mentioned in more than six decades of research and evaluations on the topic from numerous countries across the world. Based on fieldwork conducted in four primary schools in the Rakai district of Uganda, this paper attempts to demystify and critically theorise practices and ideologies of language in education. This study is inflected by the theoretical work of Tollefson (1991), particularly his challenging remark that "language is built into the economic and social structure of society so deeply that its fundamental importance seems only natural. [...] For this reason, language policies are often seen as expressions of natural, common-sense assumptions about language in society" (Tollefson 1991:2). This paper therefore sets out to surpass the mere cataloguing of problems bedevilling MT education in Uganda by proposing an account of their possible genesis. Through an examination of dysfunctional state and government structures, the role of linguistic ideology as well as the distribution of symbolic and material wealth, it is herein argued that there should be a shift from the structural-functional model, where policies are considered bodies of discourse that should, or that fail to, be implemented. It is proposed rather that the education system mirrors a wider societal concern in which colonial legacies are miserably reproduced in postcolonial Ugandan structures.